1986
DOI: 10.1002/bip.360250113
|View full text |Cite
|
Sign up to set email alerts
|

Crowned dopa's, their dimers, cyclodimers and polymers: Synthesis and cation complexation

Abstract: SynopsisOptically pure protected ~-[3,4-(1,4,7,10,13pentaoxatridecamethylene) phenyl] alanine, its dipeptide, diketopiperazine and homopolymer, protected ~-[3,4-t1,4,'7,10,13,16-hexaoxahexadecamethylene) phenyl] alanine and its polymer have been synthesized and characterized. These crown ether derivatives complex the potassium and ammonium cations as well as protonated leucine and glycine in tetrahydrofuran and methanol. They are also phase-transfer agents. The cooperativity of the crown units was studied in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Another series of aromatic hydrocarbon-containing Schiff base-bridged biscrown ethers (188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199) are listed in Table 4. Aminobenzo-15-crown-5 (Sll) was condensed with various dialdehydes to give the corresponding Schiff base-containing biscrowns 188-199 (Scheme 6, procedure I).134-136 Conductivity measurements showed that biscrowns 188-198 formed 2:1 (crown unit/cation) sandwich-type complexes with K+, Rb+, and Cs+ tetraphenyl borates, while they formed 1:1 complexes with Na+.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another series of aromatic hydrocarbon-containing Schiff base-bridged biscrown ethers (188)(189)(190)(191)(192)(193)(194)(195)(196)(197)(198)(199) are listed in Table 4. Aminobenzo-15-crown-5 (Sll) was condensed with various dialdehydes to give the corresponding Schiff base-containing biscrowns 188-199 (Scheme 6, procedure I).134-136 Conductivity measurements showed that biscrowns 188-198 formed 2:1 (crown unit/cation) sandwich-type complexes with K+, Rb+, and Cs+ tetraphenyl borates, while they formed 1:1 complexes with Na+.…”
Section: Introductionmentioning
confidence: 99%
“…Aminobenzo-15-crown-5 (Sll) was condensed with various dialdehydes to give the corresponding Schiff base-containing biscrowns 188-199 (Scheme 6, procedure I).134-136 Conductivity measurements showed that biscrowns 188-198 formed 2:1 (crown unit/cation) sandwich-type complexes with K+, Rb+, and Cs+ tetraphenyl borates, while they formed 1:1 complexes with Na+. PVC membrane K+ ionselective electrodes prepared from biscrowns [193][194][195][196][197][198] were found to have low selectivity coefficients for Na+ ions.134*135 Alkali metal ion selectivities for bilayer membranes modified by these biscrowns were investigated. 137 The crystal structures of the complexes of K+ and Rb+ picrates with biscrown 188, having a rigid m-phenylene bridge, was reported.138*139 Experimental results indicated that the intermolecular 4:2 (crown unit/cation) sandwich complexes with both K+ and Rb+ bridged biscrowns [200][201][202][203][204][205][206][207][208][209][210][211][212] in high yields (Scheme 6, procedure H).117, 118 Lockhart and co-workers108,140 designed and synthesized biscrown 213 with a polyamine bridge to provide simultaneous multiple binding sites for anions by the bridge and cations by the crown moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of DCC (N,NЈ-dicyclohexylcarbodiimide) in acetonitrile as previously described, [25] provided the diastereoisomeric amido esters (S)-Ph(OCH 3 ; (iii) (4-chlorobenzylidene)glycine tert-butyl ester, KOH powder, K 2 CO 3 , CH 2 Cl 2 , room temp. ; (iv) NH 2 OH·HCl, AcONa, 95% EtOH, room temp.…”
Section: Synthesis and Characterization Of Amino Acid Derivativesmentioning
confidence: 99%
“…They can be easily assembled in structurally well-defined, nanometer-scale, architectures of bis-crown as well as polymeric crown compounds on a peptide framework. [4][5][6] In the past few years, a series of crown-carrier derivatives of -DOPA, [4][5][6][7][8][9][10][11][12][13][14][15][16] -Lys, [17] or -Glu, [18] have been synthesized for the construction of specific peptide receptors for alkali metal, ammonium and di-ammonium ions. Application of this concept to C α -tetrasubstituted α-amino acids should result in more defined and predictable peptide structures, as ability was carried out.…”
Section: Introductionmentioning
confidence: 99%